Could Magnetic Fields Affect the Circadian Clock Function of Cryptochromes? Testing the Basic Premise of the Cryptochrome Hypothesis (ELF Magnetic Fields). Issue 1 (July 2015) - Vanderstraeten, Jacques; Burda, Hynek; Verschaeve, Luc; De Brouwer, Christophe
<x xml:space="preserve">Abstract</x> Abstract It has been suggested that weak 50/60 Hz [extremely low frequency (ELF)] magnetic fields (MF) could affect circadian biorhythms by disrupting the clock function of cryptochromes (the "cryptochrome hypothesis, " currently under study). That hypothesis is based on the premise that weak (Earth strength) static magnetic fields affect the redox balance of cryptochromes, thus possibly their signaling state as well. An appropriate method for testing this postulate could be real time or short-term study of the circadian clock function of retinal cryptochromes under exposure to the static field intensities that elicit the largest redox changes (maximal "low field" and "high field" effects, respectively) compared to zero field. Positive results might encourage further study of the cryptochrome hypothesis itself. However, they would indicate the need for performing a similar study, this time comparing the effects of only slight intensity changes (low field range) in order to explore the possible role of the proximity of metal structures and furniture as a confounder under the cryptochrome hypothesis.